African Higher Education: The Rise and Fall in the 20th Century - Mohamedbhai, Goolam (International Higher Education, 2011)
After the independence of the colonies in the 1960s, African universities became autonomous and modeled on European ones. The late 1970s and 1980s became the difficult years of economic turmoil. At the same time, a demand for higher education increased. In the 1990s, most universities in sub-Saharan Africa stood in a deplorable state. The turning point in the African universities' fates came with the UNESCO World Conference on Higher Education held in 1998, which provided a framework for renewed support to higher education and led to a revitalization of African universities.